Valinomycin: a very effective inhibitor of the cyanide-insensitive alternative pathway in plant mitochondria - Van Den Bergen, C.W.M.; Krab, K.; Wagner, A.M.; Van Der Plas, L.H.W.
The effect of valinomycin on the respiration of potato tuber callus mitochondria (Solanum tuberosum L. cv. Bintje)was investigated. The rate of electron transfer via the cytochrome pathway can be stimulated by abolishing membrane potential with valinomycin. However, valinomycin was found to inhibit CN-resistant respiration in potato tuber callus mitochondria. The inhibition is independent of the substrate used (external NADH, succinate and malate). The inhibition was enhanced by increasing the K+ concentration in the medium from 0 to 125 mM and was also observed when valinomycin was added in the presence of carbonyl cyanide 4-trifluoromethoxyphenylhydrazone (FCCP). In the presence of 125 mM K+ 1 ?M valinomycin inhibited electron flow, mediated by the alternative pathway, for approx. 65 per cent and 5 ?M valinomycin for approx. 85 percent. In mitochondria prepared from sweet potato (Ipomea batatas)valinomycin also inhibited CN-resistant respiration. © 1991 Elsevier Science Publishers B.V. All rights reserved.
Keywords: ARTICLE; ELECTRON TRANSPORT; MEMBRANE POTENTIAL; MITOCHONDRIAL RESPIRATION; MITOCHONDRION; NONHUMAN; POTATO; PRIORITY JOURNAL